OM Forum—Distributed Ledgers and Operations: What Operations Management Researchers Should Know About Blockchain Technology - Babich, Volodymyr; Hilary, Gilles (Manufacturing and Service Operations Management, 2020)
Problem definition: Blockchain is a form of distributed ledger technology. While it has grown in prominence, its full potential and possible downsides are not fully understood yet, especially with respect to operations management (OM). Academic/practical relevance: This article fills this gap. Methodology: After briefly reviewing the technical foundations, we explore multiple business and policy aspects. Results: We identify five key strengths, the corresponding five main weaknesses, and three research themes of applying blockchain technology to OM. The key strengths are (1) visibility, (2) aggregation, (3) validation, (4) automation, and (5) resiliency. The corresponding weaknesses are (1) lack of privacy, (2) lack of standardization, (3) garbage in, garbage out, (4) black box effect, and (5) inefficiency. The three research themes are (1) information, (2) automation, and (3) tokenization. Managerial implications: We illustrate these research themes with multiple promising research problems, ranging from classical inventory management, to new areas of ethical OM, and to questions of industrial organization.